2011
DOI: 10.1159/000330051
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Prevents Hyperglycemia-Induced Retinal Oxidative Stress and Inflammation in Streptozotocin-Induced Diabetic Rats

Abstract: Purpose: Our objective was to investigate the effect of green tea (GT) on diabetes-induced retinal oxidative stress and proinflammatory parameters in rats. Methods: Treatment (200 mg/kg body weight) was carried out for a period of 16 weeks in streptozotocin-induced diabetic rats and was evaluated for hypoglycemic, antioxidant [reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT)] and anti-inflammatory [tumor necrosis factor (TNF) α, vascular endothelial growth factor (VEGF)] activity. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…In accordance to our results blood glucose level of treated diabetic rat were significantly decreased when compared with diabetic group and nearly normal when compared to normal control. On the other hand serum insulin level showed statistically decrease when compared with normal control, diabetic groups showed none significant change [31,32]. These finding confirmed the opinion that Curcumin and green tea in diabetes rats cause, degradation of liver glycogen and increase gluconeogenesis, while glucose utilization is inhibited.…”
Section: Discussionsupporting
confidence: 53%
“…In accordance to our results blood glucose level of treated diabetic rat were significantly decreased when compared with diabetic group and nearly normal when compared to normal control. On the other hand serum insulin level showed statistically decrease when compared with normal control, diabetic groups showed none significant change [31,32]. These finding confirmed the opinion that Curcumin and green tea in diabetes rats cause, degradation of liver glycogen and increase gluconeogenesis, while glucose utilization is inhibited.…”
Section: Discussionsupporting
confidence: 53%
“…A more recent study investigating the possible antioxidative stress and anti-inflammatory effects for diabetic rats for 16 weeks could demonstrate the improvement of antioxidant defenses and diminishment of inflammatory markers, preventing the thickening of basement membrane 21 with a much lower dose of GT (200 mg/kg/d). Assuming equivalency on the basis of mg/m 2 , 43 the appropriate dose in an adult subject would vary from 0.7 to 0.03 g/kg/d of GT, based on data from the current study or from recently a published article, 21 respectively. From that, an adult subject should ingest from 2 to 50 g of GT per day.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds also display strong antioxidant activity [18][19][20] and anti-inflammatory effects. 21 In the context of diabetic retinal disease, it has been shown that GT not only reduces the level of anion production but also prevents the formation of acellular capillaries and pericyte ghosts. 20 EGCG also protects against brain ischemia.…”
mentioning
confidence: 99%
“…The formation of free radicals is strongly associated with lipid peroxidation and has also been implicated in the development of a variety of diseases, including cellular aging, mutagenesis, inflammation, carcinogenesis, coronary heart disease and diabetes [5]. Accumulated evidence has suggested that diabetic patients are under oxidative stress, with an imbalance between the free radical generating and radical scavenging capacities [6][7][8][9][10][11]. 15-Lipoxygenase (15-LO) and xanthine oxidase (XO) are peroxidative and prooxidative enzymes, respectively, and sources of reactive oxygen species (ROS) in vascular cells [12,13].…”
Section: Introductionmentioning
confidence: 99%